PROTAC technology for prostate cancer treatment - Zhen Wang; Dingpeng Zhang; Hiroyuki Inuzuka; Wenyi Wei (Acta Materia Medica)
Prostate cancer (PrCa) is the most prevalent urogenital cancer affecting men. PrCa is marked by uncontrolled cellular growth that leads to abnormal enlargement of the prostate gland. The metastatic spread of PrCa is the primary cause of mortality, causing cancer cell dissemination to distant sites, such as bones, the pelvis, and various visceral organs. Key contributors to PrCa progression include genetic mutations, elevated androgen receptor expression, gene amplification, and the rise of androgen receptor splice variants. Although androgen deprivation therapy remains the mainstay for early-stage PrCa treatment, efficacy is temporary because many cases advance to castration-resistant PrCa (CRPC), presenting a significant therapeutic hurdle. This review explores key biomarkers for PrCa and the latest therapeutic strategies for CRPC with a particular focus on the innovative proteolysis-targeting chimera (PROTAC) technology. This approach offers a novel means of degrading target proteins and we discuss how PROTAC holds potential as effective strategies to combat resistance mechanisms in CRPC.